2021
DOI: 10.3390/s21092944
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Six-Layer Smart Factory Architecture with Special Focus on Transdisciplinary Engineering Education

Abstract: Smart factories are an integral element of the manufacturing infrastructure in the context of the fourth industrial revolution. Nevertheless, there is frequently a deficiency of adequate training facilities for future engineering experts in the academic environment. For this reason, this paper describes the development and implementation of two different layer architectures for the metal processing environment. The first architecture is based on low-cost but resilient devices, allowing interested parties to wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 89 publications
0
4
0
2
Order By: Relevance
“…Specifically, the current literature review showed that we divide the studies of smart factories into three directions. The first stream mainly focuses on the engineering requirements of smart factories, particularly in the entire system's architecture (Ralph et al, 2021); its purpose is to bring smart factories from a conceptual idea into technical practice. The second group of studies concentrates on smart factories' use cases and technical prototypes.…”
Section: Related Studies On Smart Factoriesmentioning
confidence: 99%
“…Specifically, the current literature review showed that we divide the studies of smart factories into three directions. The first stream mainly focuses on the engineering requirements of smart factories, particularly in the entire system's architecture (Ralph et al, 2021); its purpose is to bring smart factories from a conceptual idea into technical practice. The second group of studies concentrates on smart factories' use cases and technical prototypes.…”
Section: Related Studies On Smart Factoriesmentioning
confidence: 99%
“…This applies especially to small and medium-sized enterprises (SMEs) in this specific industry segment. The required skills, as well as the necessary budget for the implementation of a state-of the-art digitalization solution are conditions that these companies often cannot fulfill, resulting in a reduction of the velocity of the digital transformation [1][2][3][4]. Additionally, in-use machine systems within this environment tend to have significantly longer life spans than other industry segments, resulting in a higher amount of mostly more complex brownfield digitization and digitalization approaches [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned, through the interaction of networked smart devices subordinate to a CPPS and linked by an IIoT, collected data can be processed through suitable computing resources, such as cloud computing services. To enable regulated access, availability and storage to data, suitable databases and corresponding DBMS must be implemented [3,26]. When selecting a suitable DBMS, it is important to pay particular attention to the system limits, as data to be processed can be too large for specific DBMSs and thus impair performance [74].…”
mentioning
confidence: 99%
“…Perusahaan membutuhkan sumber daya manusia maupun peralatan yang memadai untuk dapat melaksanakan manajemen proyek yang efektif dan efisien. Salah satu alat yang dapat digunakan perusahaan untuk mencapai tujuan ini adalah pemanfaatan sistem teknologi informasi (software) berbasis Free and Open-Source Software (FOSS) dalam melakukan interaksi, komunikasi dan kolaborasi secara internal [2][3][4][5].…”
unclassified
“…Dalam mengelola proyek, untuk mencapai kesuksesan, owner maupun kontraktor memiliki cara, strategi dan alat pendukung masing-masing. Contoh dari peralatan pendukung ini adalah software manajemen proyek [3], [6], [10]. Software manajemen proyek banyak digunakan untuk mendukung proses interaksi, komunikasi dan kolaborasi secara internal di suatu perusahaan atau organisasi (baik dari sisi owner maupun kontraktor) [11], [12].…”
unclassified